Influence of non-economic factors in the use of personal care products: the case of male Peruvian consumer - Regalado Pezúa, Otto (2016)
Over the past decade, the supply of male personal care products and services has increased considerably on a global scale. In the case of the Peruvian market, this phenomenon is still incipient despite a favorable economic outlook that has boosted the consumption in different categories. This research identifies factors that influence the consumption decision of this kind of products for the male segment. To do this, the authors used the Theory of Planned Behavior of Ajzen. The results show that male consumers´ perception of his environment (subjective norm) restrains the intention of consumption of personal care products, even though the male consumer has a positive attitude toward using of these products. These factors would reflect the existence of deeply rooted taboos in Peruvian culture, based on a traditional view of man.